2011
DOI: 10.2174/157488811795495422
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Characteristics of Bone Marrow Mesenchymal Stem Cells in Myelodysplastic Syndromes

Abstract: Myelodysplastic syndromes comprise a heterogeneous group of clonal hematopoietic stem cell malignancies characterized by ineffective bone marrow (BM) hematopoiesis, peripheral blood cytopenias and substantial risk for progression to acute myeloid leukemia. It is generally accepted that myelodysplastic syndromes originate as a result of multistep leukemogenesis, implicating genetic, epigenetic and immune-mediated alterations of an early hematopoietic stem cell. However, alterations in the BM microenvironment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 0 publications
0
23
0
5
Order By: Relevance
“…However, these authors did not study cases in relation to any specific disease group. 22,23 In other studies it was shown that MDS-MSC have reduced proliferative capacity although the investigators succeeded in expanding them in vitro. 22,24,25 Two studies by Aanei et al demonstrated again that MDS-MSC present intrinsic growth deficiencies that are related to focal adhesion protein abnormalities; the MSC from patients with refractory cytopenia (mostly LR-MDS patients) had reduced proliferation capacity while cells from patients with an excess of blasts (HR-MDS patients) had increased proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these authors did not study cases in relation to any specific disease group. 22,23 In other studies it was shown that MDS-MSC have reduced proliferative capacity although the investigators succeeded in expanding them in vitro. 22,24,25 Two studies by Aanei et al demonstrated again that MDS-MSC present intrinsic growth deficiencies that are related to focal adhesion protein abnormalities; the MSC from patients with refractory cytopenia (mostly LR-MDS patients) had reduced proliferation capacity while cells from patients with an excess of blasts (HR-MDS patients) had increased proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports state that MDS-MSC are able to sustain the growth of healthy HSPC, but the investigators did not provide a detailed analysis of different clonogenic precursor subsets according to MDS groups. 20,23,32,33 Varga et al showed that MDS-MSC provide reduced hematopoietic support. 25 Regarding the influence of MSC on CD34 + cell differentiation, we provide the first evidence of a specific deficiency of MDS-MSC correlating with disease category.…”
Section: Discussionmentioning
confidence: 99%
“…28 MSCs are present in the BM stroma to provide microenvironmental support to HPCs with whom they share an ontogenic link. 29,30 Despite MSCs sharing cytogenetic alterations with HPCs in MPN, MDS, and other hematologic disorders, [31][32][33][34] no study has been reported so far in which the presence of the KIT D816V mutation is investigated in BM MSCs from ISM patients.…”
Section: Introductionmentioning
confidence: 99%
“…This niche is responsible for mediating the direct cell contact with HSC and for supporting the selection of neoplastic hematopoietic clones [2]. Alterations in this BM microenvironment, such as abnormal interactions with HSC or malignant clones, deficient production of hematopoietic growth factors, and aberrant release of cytokines, contribute to the pathogenesis of MDS [3]. The BM microenvironment is composed of several cell types, including mesenchymal stromal cells (MSCs), which are key components in supporting self-renewal and proliferation of hematopoietic cell progenitors [4].…”
mentioning
confidence: 99%